Korelasi Karakteristik Tanah terhadap Nilai Kuat Tekan Bebas Deep Soil Mixing - Sulaiman, Muhammad; Ni’mah, Rizka Manzilatun; Pratama, Deskas Adi (Syntax Literate, 2025)
Highway infrastructure development faces significant challenges due to unstable soil conditions, which can lead to ground settlement and structural failures. One effective soil improvement method is Deep Soil Mixing (DSM), which integrates native soil with binding materials like cement to enhance load-bearing capacity. This study aims to analyze the influence of cement composition and curing duration on Unconfined Compressive Strength (UCS) in the DSM method and examine the correlation between soil parameters and stabilization outcomes. The tests were conducted with cement variations of 175 kg/m³ and 200 kg/m³ and curing durations of 7, 14, and 28 days. The results indicate that increasing cement composition significantly enhances UCS, with the 200 kg/m³ composition achieving the highest UCS of 2.10 MPa at 28 days. Additionally, UCS values from full-scale DSM work exhibited an increasing trend with curing time, with STA 17+450 recording the highest value of 2.47 MPa. Correlation analysis revealed that qc values from cone penetration tests positively correlated with UCS, whereas Plasticity Index (PI) and Fine Content showed negative correlations. Thus, DSM has proven to be an effective technique for stabilizing soft soils, and understanding soil characteristics plays a crucial role in optimizing this stabilization process.